Understanding the Crystallinity Indices Behavior of Burned Bones and Teeth by ATR-IR and XRD in the Presence of Bioapatite Mixed with Other Phosphate and Carbonate Phases - Piga, Giampaolo (2016)
We have critically investigated the ATR-IR spectroscopy data behavior of burned human teeth as opposed to the generally observed behavior in human bones that were subjected to heat treatment, whether deliberate or accidental. It is shown that the deterioration of the crystallinity index (CI) behavior sometimes observed in bones subjected to high temperature appears to be of higher frequency in the case of bioapatite from teeth. This occurs because the formation of the β-tricalcium phosphate (β-TCP) phase, otherwise known as whitlockite, clearly ascertained by the X-ray diffraction (XRD) patterns collected on the same powdered specimens investigated by ATR-IR. These results point to the need of combining more than one physicochemical technique even if apparently well suitable, in order to verify whether the assumed conditions assessed by spectroscopy are fully maintained in the specimens after temperature and/or mechanical processing.